1998
DOI: 10.1262/jrd.44.407
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Premature Luteal Regression in Ewes Superovulated with a Single Injection of Follicle-Stimulating Hormone Combined with Equine Chorionic Gonadotropin.

Abstract: Abstract. The incidence of premature corpora lutea (CL) regression was investigated in three different breeds (Merino x polled Dorset: MD, Suffolk: S, and South-Down: SD), parous and nonparous ewes (a total of 46 ewes) treated for superovulation during and out of the breeding season. Superovulation was induced with a single injection of 20 mg porcine follicle-stimulating hormone (pFSH) 2 days and 500 IU equine chorionic gonadotropin (eCG) 1 day, respectively before the removal of synthetic progestogen (40 mg F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 25 publications
3
14
0
1
Order By: Relevance
“…Our previous study [7] also showed that SD ewes showed a higher rate of corpous luteum (CL) regression than Sf and MD ewes treated with a 20 mg pFSH injection combined with 500 IU eCG. There is no report on superovulatory response in SD ewes compared with other breeds of ewes.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Our previous study [7] also showed that SD ewes showed a higher rate of corpous luteum (CL) regression than Sf and MD ewes treated with a 20 mg pFSH injection combined with 500 IU eCG. There is no report on superovulatory response in SD ewes compared with other breeds of ewes.…”
Section: Discussionmentioning
confidence: 90%
“…However, the ovarian response was greater in Merino ewes carrying Booroola gene than those with non-carriers [28]. This suggests that breed differences significantly affect the incidence of premature luteal regression [7]. It has been considered that endogenous PGF 2α and/or oxytocin arising from the response to prolonged stimulation by elevated circulating levels of E2 may be causative factors in premature luteal regression [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O fenômeno parece estar associado a elevadas concentrações plasmáticas de estrógenos durante a fase lútea inicial e, em conseqüência, nota-se um decréscimo na taxa de recuperação de embriões. Em ovelhas superovuladas, a regressão lútea precoce pode variar de 6,0% a 75,0% (FUKUI et al, 1998;LOPES Jr et al, 2006). sendo aplicado aplicado apenas uma vez ao dia, diminuindo assim os custos com este tratamento (SALLES et al, 1998).…”
Section: Regressão Lútea Precoceunclassified